1996
DOI: 10.2136/sssaj1996.03615995006000060014x
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Passive Capillary Samplers

Abstract: Soil solution samplers have certain inadequacies that limit their range of possible applications. Passive capillary samplers (PCAPS), which apply suction to the soil pore water via a hanging water column in a fiberglass wick, have shown promising results in preliminary experiments in regard to collection efficiency of water and Br tracers. The objectives of this study were to evaluate PCAPS with respect to (i) effect of installation procedure and operational characteristics; and (ii) ability to estimate the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 0 publications
1
41
0
1
Order By: Relevance
“…1). This can be explained by suction lysimeter induced lateral heterogeneity in the soil water potentials resulting in percolation flux convergence in the soil layer over WL (Holder et al, 1991) and flux divergence over GL (Brandi-Dohrn et al, 1996). The overpercolation in WL can also be explained by the possibility that the mesh samplers were of unsuitable size, as mentioned by various authors (Knutson and Selker, 1994;Lacas et al, 2004).…”
Section: Preliminary Comparison Of Fluxes Recorded In Wick and Gravitmentioning
confidence: 94%
See 1 more Smart Citation
“…1). This can be explained by suction lysimeter induced lateral heterogeneity in the soil water potentials resulting in percolation flux convergence in the soil layer over WL (Holder et al, 1991) and flux divergence over GL (Brandi-Dohrn et al, 1996). The overpercolation in WL can also be explained by the possibility that the mesh samplers were of unsuitable size, as mentioned by various authors (Knutson and Selker, 1994;Lacas et al, 2004).…”
Section: Preliminary Comparison Of Fluxes Recorded In Wick and Gravitmentioning
confidence: 94%
“…Their main weaknesses are related to the disturbance created when they are installed in the soil and to the possible differences in flow intensities and flow lines between the natural and sampled soil due to the imposed water potential condition. Among them, the zero-tension lysimeters (Boll et al, 1991;Goyne et al, 2000;Zhu et al, 2002) and the suction lysimeters (Boll et al, 1992;Brandi-Dohrn et al, 1996;Brye et al, 1999;Kosugi and Katsuyama, 2004) must be distinguished. The former sets the interface between the soil and the lysimeter at the atmospheric pressure and collects drainage water only when the soil above the interface becomes saturated.…”
Section: Introductionmentioning
confidence: 99%
“…The wick had a filament diameter of 0.7 μm, a filament tortuosity of 0.79, a porosity of 0.90, a bulk density of 0.25 g cm −3 , a diameter of 1.45 cm (Knutson and Selker, 1994), and a hydraulic conductivity of 10 −2 cm s −1 (Holder et al, 1991). Numerous studies have shown that capillary wick samplers are suitable to collect soil water and solutes (BrandiDohrn et al, 1996; Goyne et al, 2000; Louie et al, 2000). Holder et al (1991) found that adsorption of inorganic ions and selected organic chemicals to this wick material was very small.…”
Section: Methodsmentioning
confidence: 99%
“…Bromide (Br) concentration for the pan lysimeter was greater near the center of the pan, whereas Br concentration for the wick lysimeter appeared to be randomly distributed spatially. Wick lysimeters have been shown to increase collection efficiency compared to pan lysimeters (Boll et al 1991;Brandi-Dohrn et al 1996) because the wick exerts tension on the soil above the wick lysimeter, collecting water from the soil matrix that might otherwise be diverted around a pan lysimeter. The collection efficiency for two wick lysimeters in a 1-month experiment by Boll et al (1991) was 103% of water and 65% of Br compared to 25% and 7% for water and Br, respectively, for a pan lysimeter.…”
Section: Introductionmentioning
confidence: 99%